The Effect Of Role-Playing Method On The Socio-Emotional Development Of 5–6-Year-Old Children At Sasak Lestari PAUD In Academic Year 2024/2025 - harianti, Denda; Alawiyah, Tuti; Hamdani, Muh. (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract. The purpose of this study is to determine the effect of role-playing methods on the social-emotional development of 5-6-year-old children at the Sasak Lestari Early Childhood Education Center. This is a quantitative study to determine the effect of role-playing methods on the social-emotional development of 5-6-year-old children at the Sasak Lestari Early Childhood Education Center in the 2024/2025 academic year. Dusun Gereneng, Desa Anyar, Kecamatan Bayan, Kabupaten Lombok Utara In this quantitative study, a single group pretest and posttest design was used. The study consists of two variables: an independent variable and a dependent variable. The independent variable in this study is the role-playing method, while the dependent variable is social-emotional ability. The sample size is 12 students. The data collection technique used by the researcher was a pretest-posttest design, where the pretest was used to assess students' initial abilities, while the posttest was used to assess the extent of students' development after the intervention, with t-test analysis. The results of the study indicate that the application of the role-playing method on students' social-emotional skills has a significant effect.The results of the data normality test showed that the data used in this study was normally distributed according to the decision-making criteria that if the calculated r > 0.05, then the data was normally distributed. Conversely, if the sig value < 0.05, then the data was not normally distributed. In the pre-test results, the sig value was 0.936 > 0.05, so the data was normal. In the post-test results, the sig value was 0.875 > 0.05, indicating that the data is normally distributed. After implementing role-playing on children's social-emotional development, significant results were obtained, where the pre-test scores improved from 46.6 to 75, 45 to 91.6, and so on. Thus, the conclusion from this role-playing method is that there are 4 children who have begun to develop (MB), 6 children who are developing as expected (BSH), and 2 children who have developed very well. Keywords: Role-Playing Method, Children's Social-Emotional Development